A review of research on the development of inclusive education in children with special educational needs over the past 10 years: a visual analysis based on CiteSpace - Liu, Xuejiao; Potmesil, Milon (Frontiers in Education, 2025)
BackgroundChildhood is a critical developmental stage, especially for children with special educational needs (SEN), as it can profoundly affect their development and future well-being.PurposeTo assess the state of research on inclusive education for children with SEN over the last 10 years, 1,024 documents from the Web of Science (WoS) core collection were analyzed.MethodsUsing CiteSpace, a comprehensive analysis included an overview of the field, keyword distribution, research foci, and emerging trends.Results and conclusionsThis study identified that research in inclusive education for children with SEN primarily concentrates on education, psychology, and the development of children with SEN. Furthermore, future research must involve education, psychology, sociology, medicine, rehabilitation, public policy and law, neuroscience, and family studies. Primary research questions should address the effectiveness of education and learning outcomes for children with SEN, their social and emotional development, family support and participation in education, educational policy and practice, and professional development and training for inclusive education teachers. We expect that the future development of research on children with SEN will become more multidimensional and comprehensive. The research focus should shift toward comparative studies of the developmental history of special children and their peers. Methodologically, the integration of quantitative and qualitative approaches is essential. From a research perspective, a stronger emphasis should be on cross-national comparative studies. Moreover, interdisciplinary research and collaboration should be increased to enrich the theoretical and knowledge system of inclusive education for special children, thereby providing a more robust evidence base for inclusive practices.